ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI MASYARAKAT DALAM PENGEMBANGAN BANGUNAN RUMAH TIPE 36 (Studi Kasus Perumahan Surabaya Permai 4) - Ugizaqiah, Olyvia; Supriani, Fepy; Islam, Mukhlis (Universitas Bengkulu, 2020)
Abstract The increase of population caused the needed of home provider service. Mostly the housing already has it’s own type of house. As time goes by home developing happened in order to fullfill people needs. This study aimed to examine the factors that effect home development and find out the dominant factor for T36 h0use. The study uses descriptive survey methods and use multiple linear regression analysis to analyzed. Questionnaire were distributes to 41 respondents who lived in Surabaya Permai 4 Housing with 90% trust level. Processing questionnaire data using SPSS 25 with test requirements analysis, namely the validity and reliability test. The results of this research indicate that money, structural security, safety and comfort, social and culture, resident conditions, building condition effect 90.4% for home development. The most dominant factor affecting home development is the money factor with a percentage of 27.3%. The other factors are structural security 17.7%, safety and comfort 14.1%, social and culture 12.6%, resident condition 12.2% and building condition 6.5%. Keywords: house, home development, dominant factor